Sisar model for Brazil rural water supply - Carvalho, Denise; Ossewaarde, Martin J., 1965-; Yue, Tao, active 2020 (London : Rotterdam School of Management, Erasmus University, 2020)
Brazil has problems typical of both rich and poor countries, such as urban air pollution, waste management issues and obesity, but also poverty, malnutrition and lack of access to clean water and sanitation. For over two decades, its northeastern state of Ceará experimented with a novel approach to providing affordable water and sanitation services to its impoverished rural population. The community service organisation SISAR, in partnership with various governmental institutions and development banks, managed to significantly increase rural coverage of clean water. Yet about half the population in rural Ceará still had no access to clean water supply or had precarious water services.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Water-supply -- Brazil -- Case studies; Rural poor -- Brazil -- Case studies; Water-supply -- Technological innovations -- Case studies; Water-supply -- Government polivy -- Case studies